2013
DOI: 10.1080/15226514.2012.687018
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of 1,4-Dioxane-Containing Recovered Groundwater

Abstract: The results of a pilot-scale phytoremediation study are reported in this paper. Small plots of trees established on a closed municipal waste landfill site were irrigated with recovered groundwater containing 1,4-dioxane (dioxane) and other volatile organic compounds (VOCs). The plots were managed to minimize the leaching of irrigation water, and leaching was quantified by the use of bromide tracer. Results indicated that the dioxane (2.5 microg/L) was effectively removed, probably via phytovolatilization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…For example, 1,4-dioxane was applied to a phytoremediation test plot, but only 18% could be recovered compared to 86% recovery of a bromide tracer. 71 The loss of 1,4-dioxane was attributed to phytovolatilization, although no direct evidence was provided. Note that direct phytovolatilization rates are not directly comparable, as many factors affect the rate of phytovolatilization.…”
Section: ■ Transport Of Gases In Plantsmentioning
confidence: 99%
“…For example, 1,4-dioxane was applied to a phytoremediation test plot, but only 18% could be recovered compared to 86% recovery of a bromide tracer. 71 The loss of 1,4-dioxane was attributed to phytovolatilization, although no direct evidence was provided. Note that direct phytovolatilization rates are not directly comparable, as many factors affect the rate of phytovolatilization.…”
Section: ■ Transport Of Gases In Plantsmentioning
confidence: 99%
“…Studies have been carried out also on some other volatile organic compounds (VOCs) such as 1,4-dioxane. It has been found that dioxane (2.5 μg/L) was effectively removed by using phytovolatilization (Ferro et al 2013 ).…”
Section: Phytovolatilizationmentioning
confidence: 98%
“…Phytoremediation is considered a more sustainable technology because it can use locally available plants and trees to remediate contaminants and requires little energy to operate. Pilot‐scale studies have been conducted and demonstrate promise in the adsorption of 1,4‐dioxane from groundwater into the plants and subsequent transpiration via leaves (Aitchison et al., ; Ferro et al., ). Full‐scale systems are also in use.…”
Section: Overview Of Sustainability Drivers By Technologymentioning
confidence: 99%